Identifikasi Drug Related Problems (DRPs) pada Terapi Diabetes Melitus Tipe 2 di Instalasi Rawat Inap RSD dr. Soebandi Jember Periode Tahun 2015 (Identification of Drug Related Problems (DRPs) for Type 2 Diabetes Mellitus Therapy in Hospitalized Patients - Khoirotun Nazilah; Ema Rachmawati; Prihwanto Budi Subagijo (Pustaka Kesehatan, 2017)
Diabetes mellitus (DM) is a degenerative disease which causes various complications that require patients to use polypharmacy. The use of polypharmacy has been reported to be one of the causes of drug related problems (DRPs). DRPs are unexpected events related to the treatment undergone by the patient. This study aimed to avoid DRPs so that patients could receive the best treatment. This research used total sampling method and conducted retrospectively using medical records of patients with type 2 diabetes which were hospitalized in RSD dr. Soebandi Jember in 2015. As many as 15 patients (25%) of 60 patients experiencing DRPs were included in the six criteria of DRPs. This criteria included unnecessary drug therapy found in 1 patient (6,67%), need for additional drug therapy found in 1 patient (6.67%), ineffective drug found in 4 patients (26,67%) and drug interactions found in 10 patients (66.67%). Eventhough too high dosage and too low dosage was not found in all patient samples. Keywords: type 2 diabetes mellitus, drug related problems (DRPs), antidiabetic, hospitalized